Automatic Gain Control for UAV Stability Augmented System Using Jacobian Method - Suseno, Prasetyo Ardi Probo; Rizaldi, Ardian; Wijaya, Yusuf Giri; Septiyana, Angga; Pranoto, Fuad Surastyo (BRIN Publishing, 2023)
A flight control system is an important system in aircraft to direct the aircraft and maintain the aircraft’s attitudes. One of the most important parts of the flight system is the stability augmented system designed to improve the stability of the aircraft during flight. This system is usually located as the most inner-loop part of the flight control system. There are many methods to design gain control feedback for aircraft stability systems. In this paper, the longitudinal stability augmented system for Unmanned Aerial Vehicle Albatross is designed using the Jacobian methods. The Jacobian method is capable to generate feedback value automatically within the limitation given by design requirements and objectives. This method allows a faster design for the stability augmented system on multi-trim points compared to the classical method such as PID tuning. The results that the designed system works well and conforms with the design requirements and objectives.